2021
DOI: 10.3390/s21217385
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Single Trunk-Mounted Accelerometer to Detect Changes in Center of Mass Motion Linked to Lower-Leg Overuse Injuries: A Prospective Study

Abstract: Movement dynamics during running was previously characterized using a trunk-mounted accelerometer, and were associated with a history of overuse injuries. However, it remains unknown if these measures are also linked to the development of overuse injuries. The aim of this study was therefore to determine how movement dynamics alter in response to fatigue, and the possible link with developing lower-leg overuse injuries during a six-month follow-up period. Two hundred and eight movement science university stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…RMSR VT decreased, while RMSR ML and RMSR AP values increased; although, for RMSR AP , only the ALL method was significant. These results are similar to previous results [47,54], such as Winter et al [55], who reported decreased RMSR VT and increased RMSR ML . Schütte et al [48] also reported an increase in RMSR ML , and in another study, [12] reported increased RMSR ML and RMSR AP .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…RMSR VT decreased, while RMSR ML and RMSR AP values increased; although, for RMSR AP , only the ALL method was significant. These results are similar to previous results [47,54], such as Winter et al [55], who reported decreased RMSR VT and increased RMSR ML . Schütte et al [48] also reported an increase in RMSR ML , and in another study, [12] reported increased RMSR ML and RMSR AP .…”
Section: Discussionsupporting
confidence: 93%
“…There were also main effects for fatigue state for SE, with SE VT and SE RES increasing significantly, SE ML decreasing significantly, and no changes observed in SE AP . These results are similar to Pla et al [47], who demonstrated increases in SE VT with fatigue, but also observed an increase in SE AP . However, Schütte et al [12] reported contrary results, with no fatigue-related changes in SE VT or SE ML , but significant increases in SE AP .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thirty-nine features were extracted from the acceleration signals of each sample: mean, standard deviation, median, 25th percentile, 75th percentile, root mean square (RMS), maximum, minimum, sample entropy calculated from the three primary axes (vertical, medio-lateral, anterior-posterior) and the resultant (17,28,39,(42)(43)(44)(45)(46)(47)(48), and the ratio of single-axis RMS to resultant RMS (49). These features were selected based on previous analyses (31) and were identified due to their typical inclusion as features in machine learning models.…”
Section: Data Processingmentioning
confidence: 99%
“…By analysing the patterns of the acceleration and gyroscope signals of the IMUs, initial contacts and toe-offs can be detected [6,[12][13][14]. With the detection of these gait events, it is possible to subsequently calculate spatiotemporal variables, such as step rate, ground contact time, flight time, and step time [15][16][17][18][19][20], and kinematic variables, such as the vertical center of mass displacement (COM) [21]. In addition, from a kinematic parameter, such as acceleration, kinetic variables, such as ground reaction forces (GRF), shock attenuation (SA), and the peak positive attenuation of the tibia can be estimated [22].…”
Section: Introductionmentioning
confidence: 99%